2001
DOI: 10.1046/j.0014-2956.2001.02475.x
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and biochemical characteristics of poly γ‐glutamate synthetase complex of Bacillus subtilis

Abstract: An enzymatic system for poly g-glutamate (PGA) synthesis in Bacillus subtilis, the PgsBCA system, was investigated. The gene-disruption experiment showed that the enzymatic system was the sole machinery of PGA synthesis in B. subtilis. We succeeded in achieving the enzymatic synthesis of elongated PGAs with the cell membrane of the Escherichia coli clone producing PgsBCA in the presence of ATP and D-glutamate. The enzyme preparation solubilized from the membrane with 8 mM Chaps catalyzed ADPforming ATP hydroly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
129
1
3

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(139 citation statements)
references
References 43 publications
(62 reference statements)
5
129
1
3
Order By: Relevance
“…This reaction continues to polymerize c-PGA at the active site of the synthase complex (PgsBCA). PgsB and PgsC together form most parts of the complex's catalytic site, whereas PgsA seems to remove the elongated chain from the active site so that the next monomer can be added and may also be involved in transporting c-PGA (Ashiuchi et al, 2001b;Urushibata et al, 2002a). Activity of PgsBCA was found to be dependent on Mg 2+ (Ashiuchi et al, 2004).…”
Section: C-pga Polymerizationmentioning
confidence: 96%
“…This reaction continues to polymerize c-PGA at the active site of the synthase complex (PgsBCA). PgsB and PgsC together form most parts of the complex's catalytic site, whereas PgsA seems to remove the elongated chain from the active site so that the next monomer can be added and may also be involved in transporting c-PGA (Ashiuchi et al, 2001b;Urushibata et al, 2002a). Activity of PgsBCA was found to be dependent on Mg 2+ (Ashiuchi et al, 2004).…”
Section: C-pga Polymerizationmentioning
confidence: 96%
“…2). The γPGA synthetic enzyme complex was located on the cell membrane (Ashiuchi et al, 2001;Candela and Fouet, 2006), and γPGA accumulated extracellularly. Therefore, γPGA degradation may occur extracellularly.…”
Section: Discussionmentioning
confidence: 99%
“…1). PgsB is the γPGA synthase dependent on ATP (Ashiuchi et al, 1999(Ashiuchi et al, , 2001Urushibata et al, 2002) and the pgsB gene is expressed in the early stationary phase (Kimura et al, 2009). These results suggested that the accumulation of ATP and/or an intermediate of γPGA are required for γPGA synthesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5C), are synthesized by binding a γ-carboxyl group and an amino group of an adjacent glutamic acid via a hyperphosphorylated intermediate (Fig. 5D) (Ashiuchi et al, 2001). Genes related to the production of PGA were cloned and expressed well in Escherichia coli cells (Ashiuchi et al, 1999).…”
Section: Polyglutamatementioning
confidence: 99%